MEASUREMENT OF THE ARCH OF MOVEMENT OF THE CERVICAL AND LUMBAR COLUMN IN WOMEN WITH SYNDROME OF FIBROMIALGY MEASUREMENT OF THE ARCH OF MOVEMENT OF THE CERVICAL AND LUMBAR COLUMN IN WOMEN WITH SYNDROME OF FIBROMIALGY (Fiep Bulletin - online, 2015)
INTRODUCTION: The fibromialgy is a form of rheumatism that attacks woven soft of the body causing pain, to dilate, fatigues, contraction muscle, to shorten  muscle, besides upset as depression, anxiety and despair; attacking the feminine sex predominantly. OBJECTIVE: Measurement the Arch of Movement of the column (ADM) cervical and lumbar of women with fibromialgy syndrome before and after the treatment physiotherapy.  METHODOLOGY: The sample was composed by 20 subjects female, with ages between 19 and 57 years; to verify the Arch of Movement Goniômetro it was used marks Pró-Fisiomed, presenting two arms of eighteen centimeters of length and four comma five centimeters of width that it demarcates this width, with a central hole that holds and it stabilizes the arms called of fulcrum, all the subjects submitted the sessions physiotherapy of 40 minutes, twice in the week, in a period of ten weeks, receiving treatment with apparels physiotherapy ultrasound 01Mhz, it marks Ibramed - Sonopulse III, Have marks Ibramed type Physiotonus Four II, besides spine prolongations and inferior members. RESULTS: It was observed that there was increase in ADM of the cervical and lumbar column in all of the movements analisados. CONCLUSION: The found results appear for the effectiveness of that treatment verified in a second moment, powder-treatment, where it was observed that the prolongations of the cervical column in flexão, extension, right lateral deviation and left lateral deviation, as well as the prolongations of the lumbar column in flexão, extension, inclination right and lateral lateral left inclination increased, contributing satisfactorily to the increase of the movement width to articulate.
Keywords: Arch of Movement; Fibromialgia; treatment physiotherapy